2004
DOI: 10.1098/rstb.2004.1501
|View full text |Cite
|
Sign up to set email alerts
|

Water–DNA interactions as studied by X–ray and neutron fibre diffraction

Abstract: X-ray fibre-diffraction studies indicate a high degree of stereochemical specificity in interactions between water and the DNA double helix. Evidence for this comes from data that show that the molecular conformations assumed by DNA in fibres are highly reproducible and that the hydration-driven transitions between these conformations are fully reversible. These conformational transitions are induced by varying the relative humidity of the fibre environment and hence its water content. Further evidence for ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 27 publications
1
56
0
2
Order By: Relevance
“…Apart from X-ray diffraction [3,4] and multidimensional nuclear magnetic resonance [5,6], vibrational spectroscopy has been applied to identify particular functional groups along with their local interactions and to characterize different helix structures of DNA oligomers in their native aqueous environment [7,8]. The infrared spectra of DNA are highly congested with numerous overlapping absorption bands in the fingerprint range and broad, essentially structureless spectral envelopes in the range between 3100 and 4000 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from X-ray diffraction [3,4] and multidimensional nuclear magnetic resonance [5,6], vibrational spectroscopy has been applied to identify particular functional groups along with their local interactions and to characterize different helix structures of DNA oligomers in their native aqueous environment [7,8]. The infrared spectra of DNA are highly congested with numerous overlapping absorption bands in the fingerprint range and broad, essentially structureless spectral envelopes in the range between 3100 and 4000 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…A-DNA is considered to be an inactive conformation state, whereas B-DNA is associated with metabolically active DNA, and Z-DNA has been linked to regulation of DNA transcription and gene expression, perhaps affecting the binding of transcription factors (61). When a cell desiccates, the removal of DNA-stabilizing water molecules forces the native B-DNA to adopt different conformations (62), with GC-poor B-DNA forming metabolically inactive A-DNA and GC-rich B-DNA sequences tending to form Z-DNA (63,64). Furthermore, a positive correlation exists between GC content and the ability of DNA to undergo B→Z conformational transitions in genes of humans and other model vertebrates and plants (24).…”
Section: Advantages Of Gc-rich Grass Genomes Under Seasonally Cold Anmentioning
confidence: 99%
“…The sample was sealed in a flat aluminum holder, effectively fixing the humidity level, as in other, recent neutron scattering experiments [19]. The sample has been used for diffraction studies and presents a well-defined B-DNA structure, as reported by Langridge et al [20] Arnott et al [21] and more recently Fuller et al [22]. In this concentrated form of DNA, fibres are aligned to within a few degrees which is a requirement of the scattering experiment.…”
mentioning
confidence: 99%